Morphological Dynamic Study of Human Vocal Tract - Ventura, Sandra Rua (2021)
With the development of high B-value units and ultra-fast acquisition sequences, magnetic resonance imaging (MRI) has been successfully used in speech research to obtain morphological and dynamic data of the vocal tract